NEW FUNCTION
Function Expression :
\[f(x)=\frac{(x^3+x^2+x-3
)}{x+1} \]
Domain
\[\left]-\infty, -1\right[ \cup \left]-1, \infty\right[ \]
Limits
\[\lim_{x \rightarrow-\infty}f(x) = +\infty \]
\[\lim_{x \overset{<}{\rightarrow-1} }f(x) = +\infty \]
\[\lim_{x \overset{>}{\rightarrow-1} }f(x) = -\infty \]
\[\lim_{x \rightarrow+\infty}f(x) = +\infty \]
\[ \]
Derivate
\[f^{\,\prime}(x)=\frac{3 x^{2} + 2 x + 1}{x + 1} - \frac{x^{3} + x^{2} + x - 3}{\left(x + 1\right)^{2}} \]
\[f^{\,\prime}(x)=\frac{2 \left(x^{3} + 2 x^{2} + x + 2\right)}{x^{2} + 2 x + 1} \]
\[ \]
Integral
\[F(x) = \frac{x^{3}}{3} + x - 4 \log{\left(x + 1 \right)} \]
Sign Table
Variation Table
Plot
Elapsed Time: 0.0230 seconds